Breeding and lactation efficiencies and lifetime productivity of Jaffrabadi buffaloes (Indian Journal of Animal Production and Management, 2017)
Breeding efficiency and lactation efficiency during the productive herd-life along with lifetime productivity  based on 863 calving of 149 Jaffrabadi buffaloes calved and performed during 1991 to 2010 at Cattle  Breeding Farm, JAU, Junagadh were studied. Productive life, lifetime total milk production (LTMP) and  maximum standard lactation Yield (MSLMY) and association of breeding and lactation efficiencies with  production traits were also investigated. The age at first calving (AFC) and over-all calving interval (CI)  of Jaffrabadi buffaloes were, 1656.68±28.57 days (54.3months) and 541.94±7.88 days (17.8 months),  respectively. Calving interval ranged between from 532 to 558 among different lactations, the parity  effect being non-significant. In general, it increased from 1st to 4th lactation. Then after the trend was not  definite. The breeding efficiency as per Wilcox (BE-W) of the Jaffrabadi buffaloes based on all calvings  during life time averaged 74.69±2.47%. When AFC was also taken into account, breeding efficiency of  the buffaloes as per Tomar (BE-T) was estimated to be 79.04±1.46 %. About 28 % of heifers calved for  the first time below the average age of 47 months and 31 % of buffaloes calved at an average calving  interval of 15 months. Lactation period of Jaffrabadi buffaloes varied from 247.50 to 335.69 days, over-all  average being 291.87±4.96 days. The parity effect was significant (p
Keywords: Breeding efficiency; Calving Interval; Jaffrabadi buffalo; Lactation efficiency; Lactation milk Yield; Lactation period